PERBANDINGAN KADAR BESI (Fe) PADA DAUN KELOR (Moringa oleifera) YANG TUMBUH DI DATARAN TINGGI DAN DATARAN RENDAH SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Amelia Wilda Pratiwi; Nofita Nofita; Diah Astika Winahyu (Program Studi Analisis Farmasi dan Makanan Universitas Malahayati, 2021)
Moringa leaves are a multipurpose medicinal plants commonly consumed as vegetables. Moringa leaves are rich in nutrients, one of which is iron (Fe) as much as 7 mg / 100g. Iron is useful for preventing anemia. Moringa grows in the highlands and lowlands with different soil conditions, so this allows for differences in iron levels in the leaves. This study aims to determine whether there are significant differences between Moringa leaves that grow in the highlands and lowlands. Samples were obtained from one of the residents' yards in kec. Gisting (highland) and kec. Teluk Betung (lowland). The sampling technique was carried out by purposive sampling. The tools used for iron analysis are Atomic Absorption Spectrophotometry at a wavelength of 248.40 nm. Linear regression line equation is obtained, which is y = 0.010483 + 0.09074x with a correlation coefficient (r) that is 0.9985. The average level of iron from Moringa leaves that grew in the highlands and lowlands respectively 6.26 mg / 100g and 6.16 mg / 100g. The results of the calculation of the t test found that tcount = 1.06. This tcount value will be compared with ttable with a 99% confidence level of 4.60. If tcount is smaller than ttable then Ho is accepted and Ha is rejected so that there is no significant difference between iron in moringa leaves that grow in the highlands and lowlands.